2017
DOI: 10.1159/000480642
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to Severe Anemia Is Associated with Poor Functional Outcome in Acute Stroke Patients Treated with Mechanical Thrombectomy

Abstract: Background: Anemia will negatively affect cerebral collaterals and penumbra. Eventually, it may cause worse clinical outcomes and even increase mortality rates in stroke patients. Anemia has recently been suggested to be an independent risk factor for ischemic stroke. Therefore, we aimed to investigate the effects of the presence of anemia on clinical outcomes in ischemic stroke patients undergoing mechanical thrombectomy. Methods: This was a retrospective study involving the prospectively and consecutively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Our results on the effect of hemoglobin and creatinine are in line and corroborated by previous studies in stroke patients. [29,30] Mortality after MT is still relatively high considering the high reperfusion rates. The full picture of factors contributing to the higher mortality risk despite successful recanalization is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on the effect of hemoglobin and creatinine are in line and corroborated by previous studies in stroke patients. [29,30] Mortality after MT is still relatively high considering the high reperfusion rates. The full picture of factors contributing to the higher mortality risk despite successful recanalization is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to proceed with thrombectomy as part of the treatment did not influence the administration of IV rt-PA and was based on the identification of a large vessel occlusion on computerized tomographic angiography in patients presenting within 6 hours of the estimated time of onset. Exclusion criteria were as follows: <18 or >82 years, modified Rankin scale (mRS) >2, National Institutes of Health Stroke Scale (NIHSS) >25, malignancy, computerized tomography diagnosis of cerebral hemorrhage, intracerebral mass, or cerebrovascular damage secondary to trauma, presence of hemoglobinopathy (sickle cell anemia, thalassemia), anemias (hemoglobin <10 g/dL), 17 low ejection fraction (<35%), chronic kidney disease (creatinine >2 mg/dL), and posterior circulation large vessel occlusion and evidence of bone marrow insufficiency. RDW levels were measured before mechanical thrombectomy.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…4 As such, 16 clinical studies were included in this review. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The flow of studies and reasons for exclusion are shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%